Perbedaan Waktu Pengukusan Terhadap Hasil Akhir Produk Olahan Telur Asin Kelompok Pembinaan Kesejahteraan Keluarga Desa Rawa Subur, Kapuas Murung, Kalimantan Tengah - Ambar Pertiwiningrum; Ramanda Rendy Pramudya; Ratu Mutiara Kalbu; Divana Indah Permata; Annisa Dwi Nastiti (Direktorat Pengabdian kepada Masyarakat, 2023)
The village of Rawa Subur in Central Kalimantan, specifically in the Kapuas region, shows promise in the livestock sector, particularly in duck farming. Local residents process duck eggs into salted eggs to improve product marketability. The rising demand for salted eggs has driven the community to explore more efficient processing methods, including the use of ovens. The salted egg production process involves cooking at 80°C for 24 hours, followed by steaming for several hours. However, there's limited knowledge about the optimal steaming duration for achieving the best salted egg quality. This study aims to reveal the impact of varying steaming durations post-oven treatment on texture, visual appearance, and salt content in salted eggs, aiming to formulate a suitable Standard Operating Procedure (SOP). Using a completely randomized design, the study includes four steaming duration treatments (0, 2, 4, 6 hours) after a 24-hour oven treatment. Simple Linear Regression analyzes the data to identify the relationship between steaming duration variations and salt content. Laboratory tests show that salt content in salted eggs for steaming durations (0, 2, 4, 6 hours) is 16.85%, 20.97%, 22.33%, and 24.87%, respectively, with a Significance (Sig.) value of 0.021 (<0.05). This confirms that steaming duration significantly influences salt content. Detailed analysis reveals a substantial impact of steaming duration on salt content, accounting for 95.8%, as indicated by the coefficient of determination (R-squared) value of 0.958. In conclusion, prolonged steaming increases salt content in salted eggs. In response, the Village Family Welfare Development Group in Rawa Subur has begun implementing SOPs for food processing, involving the use of ovens and steaming for four hours.